Pemahaman Sustainable Development Goals (SDGs) Berbasis Poster Canva Melalui Problem Based Learning (PBL) Pada Peserta Didik SMP - Rabiul Awwal; Khirjan Nahdy; Baiq Rismarini Nursaly; Badarudin Badarudin (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study aims to: (1) identify students’ understanding of Sustainable Development Goals (SDGs) at SMP Negeri 2 Suralaga, (2) describe the implementation of Canva-based poster media in understanding SDGs, and (3) analyze the implementation of Problem-Based Learning (PBL) integrated with Canva-based posters in enhancing students’ understanding of SDGs. This research employed a descriptive qualitative approach. The participants of this study were eighth-grade students of SMP Negeri 2 Suralaga. Data were collected through observations, interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that students’ understanding of Sustainable Development Goals (SDGs) was generally categorized as good. Students were able to recognize the basic concepts of SDGs, understand several sustainable development goals, and relate them to their daily lives. The implementation of Canva-based poster media contributed positively to the learning process by attracting students’ attention, facilitating comprehension, improving memory retention, and increasing learning motivation. Furthermore, the implementation of Problem-Based Learning (PBL) integrated with Canva-based poster media enhanced students’ participation in discussions, critical thinking skills, collaborative learning, and problem-solving abilities related to SDGs issues. The combination of PBL and Canva-based posters created a more interactive, creative, contextual, and meaningful learning environment, enabling students to develop a deeper understanding of Sustainable Development Goals (SDGs).